Generative Art and Secondary Education: Impact of Artificial Intelligence Tools on Student Creativity - Galindo Duran; Alejandro Alejandro (Yayasan Adra Karima Hubbi, 2024)
Background. This research analyzes the impact on creativity of different Artificial Intelligence tools applied to secondary education, specifically in the artistic field.Purpose. This research analyzes the impact on creativity of different Artificial Intelligence tools applied to secondary education, specifically in the artistic field. Method. Publications comparing traditional methods with AI-based methodologies have been analyzed in detail through statistical analysis.Results. The results show significant improvements in student creativity, as well as a democratization of art. After obtaining an average positive impact of 0.4893 (p < 0.001), and a high degree of heterogeneity (I² = 90.84%). Conclusion. Despite the variety of contexts and methodologies used in each of the articles analyzed, there is an improvement in creativity, critical thinking or problem solving.